2020
DOI: 10.1093/femsec/fiaa226
|View full text |Cite
|
Sign up to set email alerts
|

AHL-priming for enhanced resistance as a tool in sustainable agriculture

Abstract: Bacteria communicate with each other through quorum sensing (QS) molecules. N-acyl homoserine lactones (AHL) are one of the most extensively studied groups of QS molecules. The role of AHL molecules is not limited to interactions between bacteria; they also mediate inter-kingdom interaction with eukaryotes. The perception mechanism of AHL is well-known in bacteria, and several proteins have been proposed as putative receptors in mammalian cells. However, not much is known about the perception of AHL in plants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 172 publications
0
9
0
5
Order By: Relevance
“…While Liu et al [34] observed that AHLs with short side chains stimulate root length and antioxidative capacities in barley leaves [35]. A review done by Shrestha and Schikora [15] explains that there are 'AHL-primable' and 'AHL-non-primable' types depending on the response of plants through AHL priming. It has yet to be seen whether ginseng is a possible 'AHL-primable' crop, although our phenotypic results proved to be an excellent example of good ginseng growth when treated with AHLs, as can be determined by the data presented in Figure 1 and Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Liu et al [34] observed that AHLs with short side chains stimulate root length and antioxidative capacities in barley leaves [35]. A review done by Shrestha and Schikora [15] explains that there are 'AHL-primable' and 'AHL-non-primable' types depending on the response of plants through AHL priming. It has yet to be seen whether ginseng is a possible 'AHL-primable' crop, although our phenotypic results proved to be an excellent example of good ginseng growth when treated with AHLs, as can be determined by the data presented in Figure 1 and Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Quorum sensing (QS) is a process through which bacteria attain intercellular communication. The production and detection of autoinducer signaling molecules make it possible for bacteria to observe cell density and coordinate behavioral changes collectively [15]. Signaling molecules allow for gene regulation to occur within the population, allowing the bacterial community to regulate cellular processes-such as biofilm formation, motility, sporulation, and virulence-which are important for survival and adaptation in the environment [16].…”
Section: Introductionmentioning
confidence: 99%
“…С6-АГЛ способны стимулировать процессы роста и корнеобразования (90,98,99), а также индуцировать системную устойчивость к широкому спектру патогенов у многих видов растений (100). Таким образом, различные исследования продемонстрировали, что бактериальные АГЛ могут быть использованы для улучшения роста и повышения урожайности растений, снижения зависимости от фунгицидов и удобрений, для борьбы с патогенами и стрессорами (101).…”
Section: рис 2 физиолого-биохимические процессы индуцируемые ацилгомосеринлактонами (агл)unclassified
“…С6-АГЛ способны стимулировать процессы роста и корнеобразования (90,98,99), а также индуцировать системную устойчивость к широкому спектру патогенов у многих видов растений (100). Таким образом, различные исследования продемонстрировали, что бактериальные АГЛ могут быть использованы для улучшения роста и повышения урожайности растений, снижения зависимости от фунгицидов и удобрений, для борьбы с патогенами и стрессорами (101).…”
unclassified